Transcriptional Feedback Loops in the Caprine Circadian Clock System - Gao, Dengke; Zhao, Hongcong; Dong, Hao; Li, Yating; Zhang, Jing; Zhang, Haisen; Zhang, Yu; Jiang, Haizhen; Wang, Xiaoyu; Wang, Aihua; Jin, Yaping; Chen, Huatao (Frontiers in Veterinary Science, 2022)
The circadian clock system is based on interlocked positive and negative transcriptional and translational feedback loops of core clock genes and their encoded proteins. The mammalian circadian clock system has been extensively investigated using mouse models, but has been poorly investigated in diurnal ruminants. In this study, goat embryonic fibroblasts (GEFs) were isolated and used as a cell model to elucidate the caprine circadian clock system. Real-time quantitative PCR analysis showed that several clock genes and clock-controlled genes were rhythmically expressed in GEFs over a 24 h period after dexamethasone stimulation. Immunofluorescence revealed that gBMAL1 and gNR1D1 proteins were expressed in GEFs, and western blotting analysis further verified that the proteins were expressed with circadian rhythmic changes. Diurnal changes in clock and clock-controlled gene expression at the mRNA and protein levels were also observed in goat liver and kidney tissues at two representative time points in vivo. Amino acid sequences and tertiary structures of goat BMAL1 and CLOCK proteins were found to be highly homologous to those in mice and humans. In addition, a set of goat representative clock gene orthologs and the promoter regions of two clock genes of goats and mice were cloned. Dual-luciferase reporter assays showed that gRORα could activate the promoter activity of the goat BMAL1, while gNR1D1 repressed it. The elevated pGL4.10-gNR1D1-Promoter-driven luciferase activity induced by mBMAL1/mCLOCK was much higher than that induced by gBMAL1/gCLOCK, and the addition of gCRY2 or mPER2 repressed it. Real-time bioluminescence assays revealed that the transcriptional activity of BMAL1 and NR1D1 in goats and mice exhibited rhythmic changes over a period of approximately 24 h in NIH3T3 cells or GEFs. Notably, the amplitudes of gBMAL1 and gNR1D1 promoter-driven luciferase oscillations in NIH3T3 cells were higher than those in GEFs, while mBMAL1 and mNR1D1 promoter-driven luciferase oscillations in NIH3T3 cells had the highest amplitude. In sum, transcriptional and translational loops of the mammalian circadian clock system were found to be broadly conserved in goats and not as robust as those found in mice, at least in the current experimental models. Further studies are warranted to elucidate the specific molecular mechanisms involved.